Renin-angiotensin-aldosterone system in ISIAH rats with stressinduced arterial hypertension - A. D. Dubinina; E. V. Antonov; L. A. Fedoseeva; E. N. Pivovarova; A. L. Markel; L. N. Ivanova (Вавиловский журнал генетики и селекции)
Because the renin-angiotensin system (RAS) has a wide range of opportunities in the regulation of fluid and electrolyte balance and arterial pressure, it is currently hypothesized that alterations in systemic circulating or local tissue RAS are some of the most important pathogenetic factors in the development of essential hypertension. The aim of the study was to investigate circulating and local tissue RAS activities in ISIAH rats with stress-induced arterial hypertension. We estimated the serum levels of renin, the angiotensin-converting enzyme, angiotensin II and aldosterone by an enzymelinked immunosorbent assay, and mRNA expression of RAS genes in kidney, adrenals and brain tissues was measured by the real-time polymerase chain reaction. The mRNA expression of the renin gene (Ren) in the ISIAH rats was significantly decreased as compared to the normotensive WAG rats, but plasma renin concentrations had no difference. At the same time, the serum levels of angiotensin II and aldosterone in the ISIAH rats were enhanced, which suggests the existence of an ectopic site of angiotensin synthesis. Expression of RAS genes in the adrenals of hypertensive rats was unchanged. By contrast, a significant increase of RAS genes expression was found in the brain tissues. The mRNA of the Ren gene was increased in the hypothalamus, and the mRNA of Ace gene was increased in the brain stem of the ISIAH rats. This may be indicative of a local increase of RAS activity in the brain tissues of ISIAH rats. Nevertheless, the results of the study define ISIAH rat strain as a model of human low-renin hypertension.